Aerosol risk with noninvasive respiratory support in patients with COVID‐19. Issue 4 (10th June 2020) - Miller, David C.; Beamer, Paloma; Billheimer, Dean; Subbian, Vignesh; Sorooshian, Armin; Campbell, Beth Salvagio; Mosier, Jarrod M.
Abstract: Objectives: This study evaluates aerosol production with high‐flow nasal cannula (HFNC) and noninvasive positive pressure ventilation (NIPPV) compared to 6 L/min by low‐flow nasal cannula. Methods: Two healthy volunteers were randomized to control (6 L/min by low‐flow nasal cannula), NIPPV, or HFNC using block randomization. NIPPV conditions were studied using continuous positive airway pressures of 5, 10, and 15 cm H2 O with an FiO2 of 1.0 delivered via full‐face mask. HFNC conditions included flow rates of 30 and 40 L/min with an FiO2 of 1.0 with and without coughing. HFNC and low‐flow nasal cannula conditions were repeated with and without participants wearing a surgical mask. Six aerosol sizes (0.3, 1.0, 2.5, 5, and 10 µm) and total aerosol mass were measured at 2 and 6 ft from the participant's nasopharynx. Results: There was no significant difference in aerosol production between either HFNC or NIPPV and control. There was also no significant difference with the use of a procedural mask over the HFNC. There was significant variation between the 2 participants, but in neither case was there a difference compared to control. There was an aerosol‐time trend, but there does not appear to be a difference between either flow rate, pressure, or control. Furthermore, there was no accumulation of total aerosol particles over the total duration of the experiment in both HFNC and NIPPV conditions. Conclusions: HFNC and NIPPV did not increase aerosol production compared to 6 L/min by low‐flow nasal cannula in this experiment involving healthy volunteers.